The impact of maternal nutritional status on fetal weight and long-term repercussions: Systematic review - Moura , Francini Viscondi Lopes e; Jamberci , Ana Flavia Aggio; Mendes , Biancca Bavelloni; Moura, Sabrina Viscondi Lopes e; Brunherotti, Marisa Afonso Andrade (Seven Editora, 2023)
Maternal nutritional status is an indicator of long-term health maintenance, both for the mother and for the child, and the great challenge during the pregnancy period is to maintain it adequate, with an effective supply of nutrients, that is, to provide enough energy supply to maintain a pregnant woman’s body mass index within the parameters considered ideal and allow adequate growth of the fetus. Injuries during pregnancy, especially when related to maternal overweight or malnutrition, cause fetal metabolic reprogramming leading to cell hyperplasia or energy-saving fetus, respectively, causing a greater risk of metabolic and cardiovascular diseases. In addition, vitamin deficiencies such as folic acid and iron, among others, are harmful to the fetus, with a greater risk of defects in neural tube closure and anemia, and supplementation is recommended. In this way, monitoring during the prenatal period allows a follow-up of this pregnant woman so that she receives guidance and better control of her nutritional balance to prevent harm to the health of the binomial. DOI:https://doi.org/10.56238/alookdevelopv1-157